2018
DOI: 10.1016/j.yhbeh.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' cortisol and testosterone in the days around infants' births predict later paternal involvement

Abstract: Human paternal behavior is multidimensional, and extant research has yet to delineate how hormone patterns may be related to different dimensions of fathering. Further, although studies vary in their measurement of hormones (i.e., basal or reactivity), it remains unclear whether basal and/or reactivity measures are predictive of different aspects of men's parenting. We examined whether men's testosterone and cortisol predicted fathers' involvement in childcare and play with infants and whether fathers' testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 44 publications
3
59
2
Order By: Relevance
“…While these findings ostensibly conflict with the patterns we documented among Bondongo fathers, they are potentially congruent because of the distinction between basal hormone production and shorter-term reactivity (Kuo et al, 2018;Trumble et al, 2015). Based on existing models (van Anders et al, 2011;Crespi, 2016), we suggest it is plausible that in socially hierarchical contexts such as among the Bondongo and Tsimane (von Rueden et al, 2011), men who are ranked highly for dominance and status will tend to have elevated basal T and reduced basal OT, but will show short-term rises in OT production in response to socially rewarding contexts pertaining to status (e.g., hunting for Tsimane men).…”
Section: Fathers' Ot and Joint Profiles For Ot And Tcontrasting
confidence: 95%
See 4 more Smart Citations
“…While these findings ostensibly conflict with the patterns we documented among Bondongo fathers, they are potentially congruent because of the distinction between basal hormone production and shorter-term reactivity (Kuo et al, 2018;Trumble et al, 2015). Based on existing models (van Anders et al, 2011;Crespi, 2016), we suggest it is plausible that in socially hierarchical contexts such as among the Bondongo and Tsimane (von Rueden et al, 2011), men who are ranked highly for dominance and status will tend to have elevated basal T and reduced basal OT, but will show short-term rises in OT production in response to socially rewarding contexts pertaining to status (e.g., hunting for Tsimane men).…”
Section: Fathers' Ot and Joint Profiles For Ot And Tcontrasting
confidence: 95%
“…In one of the only prior naturalistic studies of OT in a small‐scale society that emphasizes fathers' provisioning, Jaeggi et al () found that Tsimane foragers' salivary OT increased across a multiple‐hour hunting expedition. In this study, men who exhibited greater OT increases during the hunt likewise showed larger elevations in T. While these findings ostensibly conflict with the patterns we documented among Bondongo fathers, they are potentially congruent because of the distinction between basal hormone production and shorter‐term reactivity (Kuo et al, ; Trumble et al, ). Based on existing models (van Anders et al, ; Crespi, ), we suggest it is plausible that in socially hierarchical contexts such as among the Bondongo and Tsimane (von Rueden et al, ), men who are ranked highly for dominance and status will tend to have elevated basal T and reduced basal OT, but will show short‐term rises in OT production in response to socially rewarding contexts pertaining to status (e.g., hunting for Tsimane men).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations